Das Wort als Verwirklichung des chassidischen Mythos in den Erzählungen Martin Bubers - Dzikowska, Katarzyna (Studia Germanica Posnaniensia, 2018)
Die Erzählungen der Chassidim („The stories of Chassidim“) of Martin Buber open to a reader an approach to a reality, for which a word is the basis of existence. A word becomes a myth, which in its turn determines human existence in an absolute way. It is a living, sacred word; the respect should be given to it, as it comes from God Himself. The Chassidic myth cannot be treated as a phantasy, it belongs totally to the spiritual world of a Jewish people who's history is a word, coming into being between two persons, a history of unceasing dialog between God and man. The French representative of structuralism Roland Barthes elucidates the relation between a word and a myth with semiological categories. As he notices, however, such an analytical treatment of .myth destroys it, e.g. makes it impossible for somebody to experience the reality, hidden in the word. That is why, though Buber's stories fulfill the postulates of Barthes, only the trustful acceptance of a word is a way of getting to know the plenitude of a Chassidic myth.